2007 International Symposium on Signals, Circuits and Systems 2007
DOI: 10.1109/isscs.2007.4292712
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Image Annotation Combining the Content and the Context of Medical Images

Abstract: In this paper we evaluate the relevance of the extracting image-related information [3] [4]. More recently, information extracted from the visual content of medical im-content-based image description, annotation, indexing and ages and from the image-related text-regions, as well as the retrieval methods were proven to be powerful tools when performance gain obtained by combining the two approaches. searching for images in non-annotated databases [5], [6]. Over First we annotate the images using a content-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The combination of methods relating to image content and context has been identified as a possible means to bridging the semantic gap in multiple domains (Florea, Buzuloiu, Rogozan, Bensrhair, & Darmoni, ; Tuffield et al., ; Smeulders et al., ). One particular type of context, which multiple authors have identified as relevant, is location.…”
Section: Related Work On Image Indexing and Retrievalmentioning
confidence: 99%
“…The combination of methods relating to image content and context has been identified as a possible means to bridging the semantic gap in multiple domains (Florea, Buzuloiu, Rogozan, Bensrhair, & Darmoni, ; Tuffield et al., ; Smeulders et al., ). One particular type of context, which multiple authors have identified as relevant, is location.…”
Section: Related Work On Image Indexing and Retrievalmentioning
confidence: 99%
“…One solution to this problem is the use of ML tools capable of labeling weighting and sequence type. Related works have proposed ML models that label MR sequences, some by looking directly at the images as matrix data [12]- [14], while others make use of the DICOM metadata [15]- [17]. Solutions that use the DICOM metadata as inputs usually offer very short inference times and require less computational power (no GPU needed) than image-based solutions (that use matrices as input) since metadata inferences are simpler.…”
Section: Introductionmentioning
confidence: 99%
“…Current research in the biomedical domain (e.g., Florea et al, 2007), has investigated hybrid approaches to image retrieval, combining elements of content-based image retrieval (CBIR) and annotation-based image retrieval (ABIR). ABIR, compared to the image-only approach of CBIR, offers a practical advantage in that queries can be more naturally specified by a human user (Inoue, 2004).…”
Section: Introductionmentioning
confidence: 99%